Analysis of genetic tendencies in fruit traits of macadamia hybrid F1 generation - LI Zhiqiang; WU Chao; MA Jing; LI Tingyu; LI Yang; TAO Liang; GONG Lidan (Guoshu xuebao)
[Objective] China has the largest area of macadamia cultivation. Extensive research on the genetic tendencies of key traits in the crop has been widely conducted. This study analyzed the variation and genetic tendencies of traits related to the fruits of hybrid F1 generation of macadamia, in order to offer valuable insights of the inheritance patterns of these traits and to select hybrid parent materials for hybridization. [Methods] Three hybrid combinations of macadamia varieties, O.C, 863 and 344 were utilized to create a total of 275 F1 individuals, including 89 offspring from the combination O.C (♀) × 344 (♂), 78 from O.C (♀) × 863 (♂), and 108 from 863 (♀) × O.C (♂). Cross pollination was carried out in 2011 and seedlings from the crosses were planted in 2012 at the seed selection nursery of the Yunnan Institute of Tropical Crops, and the trees have now all entered their peak production phase. Sixty mature fruit were selected from each lineage exhibiting normal growth, and 12 quantitative traits were measured, including fruit transverse diameter, husk thickness, nut transverse diameter, nut longitudinal diameter, kernel recovery, total sugar content, protein content, oil content, oleic acid content, linoleic acid content, alpha-linolenic acid content, and palmitoleic acid content. Phenotypic traits were measured using calipers, while nut quality traits were assessed using near-infrared grain analyzer (FOSS DS2500, USA). Raw data were recorded and processed using Office 2007. Statistical analysis and Pearson correlation analysis were conducted using SPSS 20 software. The statistical indicators included the coefficient of variation (CV), mid-parent heterosis (MPV), high-parent heterosis (BPH), low-parent heterosis (LPH), and the relative heritability of the male parent (af) and female parent (am). Frequency distribution and correlation plots of the fruit-related traits were treated using Origin 2021 and R, respectively. [Results] The results indicated that the coefficient of variation for the 12 traits ranged from1.60% to 27.10%. Among the average coefficients of variation across the three hybrid combinations, the highest variation was observed in linoleic acid content (23.37%), followed by total sugar (21.28%), alpha-linolenic acid (16.35%), kernel recovery (15.50%), husk thickness (13.32%), nut longitudinal diameter (8.03%), nut transverse diameter (7.05%), protein content (6.66%), palmitoleic acid (6.59%), fruit transverse diameter (6.31%), oleic acid (4.05%), and oil content (1.93%). The mid-parent heterosis for the 12 quantitative traits in the hybrid offspring ranged from-30.89% to 31.06%, while the high-parent heterosis varied from-33.75% to 27.94%, and the low-parent heterosis spanned from-29.49% to 34.33%. Analysis of genetic parameter revealed that five traits, including fruit diameter, shell thickness, shell diameter, shell length, and oleic acid content, exhibited negative high-parent heterosis, suggesting that these traits demonstrate negative super-parental inheritance in the hybrids. Conversely, four traits including kernel yield, oil content, protein content, and linoleic acid content, displayed negative mid-parent heterosis and positive low-parent heterosis, indicating that these traits manifest a tendency towards lower genetic characteristics in the hybrid offspring. Palmitoleic acid content exhibited negative high-parent heterosis but positive mid-parent heterosis, suggesting a trend towards higher genetic characteristics. Additionally, total sugar content and alpha-linolenic acid content both showed positive high-parent heterosis, indicating their positive super-parental inheritance characteristics. The relative heritability of the 12 quantitative traits across the three hybrid combinations indicated that five traits, including kernel yield, oil content, protein content, linoleic acid content, and palmitoleic acid content, exhibited positive heritability values, indicating these 5 traits exhibited partial dominance in the hybrid offspring. The remaining seven traits had a relative heritability greater than 1 in the parents, suggesting the presence of super-dominant inheritance. Additionally, when the parent 863 was used both as the maternal and paternal line, it demonstrated higher relative heritability. Among the nine traits, including shell thickness, shell length, kernel yield, oil content, protein content, total sugar content, oleic acid content, linoleic acid content, and palmitoleic acid content, all showed a normal distribution across the three hybrid combinations (p>0.05). Traits such as fruit diameter and shell diameter in the combination O.C × 344 displayed extreme values and exhibited a skewed distribution, whereas the other two hybrid combinations showed normal distribution patterns. Alpha-linolenic acid content displayed a bimodal or skewed distribution across all three hybrid combinations. Among the five fruit phenotypic traits, fruit diameter, shell diameter, and shell length exhibited strong positive correlation with each other, while shell thickness demonstrated a negative correlation with kernel yield. Among the seven traits related to kernel components, oil content was positively correlated with linoleic acid content and alpha-linolenic acid content, yet negatively correlated with the other four traits. Protein content exhibited a moderate negative correlation with alpha-linolenic acid content. Oleic acid content was negatively correlated with palmitoleic acid content, while linoleic acid content was positively correlated with alpha-linolenic acid content but negatively correlated with palmitoleic acid content. [Conclusion] The variation among the 12 traits in the hybrid F1 population of macadamia varied significantly, and demonstrated different genetic tendencies. Most traits conformed to the characteristics of quantitative traits controlled by multiple genes. Notably, there were 34 pairs of traits exhibiting significant or extremely significant correlations among the 12 traits, with the numbers of positive and negative correlations being approximately equal. Traits related to kernel composition generally displayed moderate or weak correlations.